Methodological Bases of Sociopragmatic Study of Literary Text - YULDASHEVA, KHALIDA (The journal of contemporary issues in business and government, 2021)
This article discusses sociopragmatic analysis, a branch of pragmalinguistics, and the methodological foundations of the sociopragmatic study of literary texts. Sociopragmatism is one of the most important branches of linguistics, which makes its aspects more visible in the literary text. for this reason it is characterized by the high importance of communicative pragmatics and sociopragmatics in text analysis.